2008
DOI: 10.1016/j.ophtha.2008.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors Affecting Visual Outcome in Acanthamoeba Keratitis

Abstract: Objective-To identify clinical and demographic factors associated with a worse visual outcome in Acanthamoeba keratitis (AK).Design-Retrospective, case control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
110
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 16 publications
9
110
2
1
Order By: Relevance
“…Our observation is nevertheless consistent with other reports, which have shown that use of topical corticosteroids before acanthamoeba diagnosis and treatment may lengthen the duration of infection. 7,22,23 We also found that eyes with stromal involvement at presentation seemed to have longer microbial clearance times compared with those without stromal involvement, though this too lacked statistical significance. This finding is consistent with previous studies that have shown an association between deep stromal keratitis and worse disease outcomes.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Our observation is nevertheless consistent with other reports, which have shown that use of topical corticosteroids before acanthamoeba diagnosis and treatment may lengthen the duration of infection. 7,22,23 We also found that eyes with stromal involvement at presentation seemed to have longer microbial clearance times compared with those without stromal involvement, though this too lacked statistical significance. This finding is consistent with previous studies that have shown an association between deep stromal keratitis and worse disease outcomes.…”
Section: Discussionmentioning
confidence: 77%
“…This finding is consistent with previous studies that have shown an association between deep stromal keratitis and worse disease outcomes. 3,7 In this report, we estimate that the median clearance time of acanthamoeba from corneas treated with standard anti-acanthamoebal medications is 42.5 days (IQR 22-82 days). This indicates that 50% of our cases cleared between 4 and 12 weeks, though clearly the duration of treatment should be tailored for each individual case.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Disease severity can range from relatively minor epithelial and subepithelial diseases, which respond well to treatment, to refractory disease that can provoke corneal melting and perforation requiring therapeutic or tectonic corneal grafts (13). Currently, the most important factors affecting the prognosis are disease severity at presentation and the interval between symptom onset and the start of effective therapy (14,15); beginning therapy Ͼ3 weeks after symptom onset is associated with a worse prognosis.…”
mentioning
confidence: 99%